BUDAYA ORGANISASI, SISTEM PENGHARGAAN DAN EFEKTIVITAS ORGANISASI - Risa Cesilya (JIANA ( Jurnal Ilmu Administrasi Negara ), 2015)
Organizational Culture, Systems and Organizational Effectiveness Awards. The aim was to determine the influence of organizational culture and reward systems for organizational effectiveness at PT. Regional PLN Riau, Pekanbaru branch. The population is all employees, consisting of 64 employees were selected using census method. The technique of collecting data using questionnaires, observations and interviews. Data were analyzed using linear regression. These results indicate that the influence of culture and reward system simultaneously and partially on the effectiveness of the organization. Stronger influence of organizational culture on organizational effectiveness than the influence exerted by the award system.